Cross-Cultural Mission Strategy in Balinese Culture - Hun, Kang Yong; Hidayati, Ermin; ndun, yusak; Nehe, Restuman (EUNOIA Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
This article aims to research the Balinese tribes in the Hindu cultural region and find mission methods that suit the Balinese tribes. Research on these tribes is crucial in finding effective mission methods. This is because an understanding of the people, religion, culture, and tribal worldview can help find a good point of contact for a successful mission. The author has investigated the Balinese tribe from a social, religious, and cultural perspective. In particular, Balinese Hindu traits have been identified and analyzed, as well as the Hindu social structure, caste system, and local communities and rituals in Bali have been investigated. Research on the history of missions in Bali is also carried out to find obstacles in missions in Bali, reduce mistakes in facing new mission challenges, and find effective and implementable mission activities. The history of missions in Bali may be short, but it is full of suffering and tears. However, at the same time, a spark of hope can be found that is not extinguished in the midst of adversity. The Trinity of God in His mission, the author analyzes the 'role of the Holy Spirit', emphasizing the Holy Spirit at work in Bali. The author focuses on the Trinity relationship of God to communicate the importance of the mission attitude that wants to communicate through the relationship. This is linked to 'mission contextualization', and the author mentions a model of contextualization that leads towards physical spiritual unity. We also investigated the concept of 'Missionary Church' and how it can be applied in cross-cultural mission sites. Regarding the 'mission for the weak', the author analyzes Jesus' mission to the poor, marginalized, and weak, and mentions the importance of mission for them today. In addition, we mentioned the advantages of the peripheral mission model that can be applied in Bali, especially in orphanage services, and we present the future direction for orphanage services in Bali that are currently operating. Before offering practical mission methods, the author has done a theological reflection on the mission of the Triune God, the contextualization of missions, the mission church, and missions for the weak. The author also proposes an independent mission church model in the form of a cooperative and proposes the mission of Christian schools as part of the educational mission. Now, through the study of the mission of the Balinese tribe in the Hindu cultural region of Bali, it can be concluded that God's mission can be accessed through the view of Jesus Christ in the flesh. In other words, when we have an attitude of loving and respecting the Balinese tribe with the heart of Jesus Christ, we can find the mission connection point and achieve the mission results.